Analisis Makna Kewajiban Rehabilitasi Medis Terhadap Pecandu Narkotika (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The application of sanctions on narcotics is quite serious, but in fact the perpetrators of crimes are increasing, and for convicts in practice it is inconclusive and prone to recidivism. This can be caused because the criminal conviction by the judge has no impact or is slow on the culprit. So far, judges tend to emphasize more on criminal sanctions, if it is worth the behavior of the perpetrator with the aim that the perpetrator does not repeat his behavior. This can be caused by the existence of a criminal conviction factor by a judge that does not have an impact or deferrent effect on the perpetrators. So far, criminal convictions by judges tend to prioritize criminal sanctions that are worth the perpetrator's actions, with the aim that the perpetrator does not repeat his actions. In general, drug addicts and victims of narcotics crimes have not received access to rehabilitation services, especially drug addicts and victims of narcotics crimes who are in prisons and detention centers. Therefore, the emphasis of the formulation in this study is how to analyze the significance of medical rehabilitation obligations for drug addicts. The methods used in this study are normative methods and approaches to the method of the statutory approach (Statue Approach) and Conceptual Approach (Conceptual Approach) The results of the study found that Makana Medical Rehabilitation Obligations Against Narcotic Addicts are